Torsional Modeling of Reinforced Concrete Beam–Column Joint Retrofitted by Aramid Fiber—Experimental and Numerical Analysis - Palaniappan Prasath; Ravindran Gobinath; Jayaprakash Sridhar (Advances in Civil Engineering)
The performance of structural composites during loading has always been a concern for the designers and construction industry since the reinforced concrete structure was discovered. In this study, lateral load–displacement behavior of beam–column joints wrapped with aramid fiber is evaluated using both experimental and numerical analysis subjected to torsional moment (beam-eccentric loading). Three categories of reinforcement concepts are adopted for the preparation of the beam–column joints, where members are wrapped with aramid fiber at the joints, and others are not fortified with aramid fibers. Prior to testing, the structural composites are cured for maximum 28 days into water. The beam–column joints are subjected to lateral load at a point near the column end of the beam–column connection, and the corresponding deflections are measured until the member fails. Based on the test results, ductility and energy absorption capacity are evaluated. The findings of the numerical investigation of beam–column joint show there is not much variation in the experimental and numerical analysis; it is clearly found that aramid fiber wrapping provided large rigidity in the joint, and it is also prolonged the final failure of the joints. This study shows that in addition to the conventional reinforcement, providing the hanger reinforcement and the diagonal reinforcement improves the rigidity of the beam–column joints during severe loadings, as this study described.